Improving the ability of families and patients to prevent recurrence through health education - Muhammad Khoirul Amin; Sambodo Sriadi Pinilih (Universitas Muhammadiyah Magelang, 2022)
Cadres and families are the closest people to People with Mental Disorders (ODGJ) in public life. However, it should be noted that there are problems experienced by some of the cadres or families, namely the symptoms of ODGJ who experience recurrence. Thus, it is often considered to add to the burden on the family. The purpose of this service activity is to assist families in preventing the recurrence of ODGJ assisted by the role of mental health cadres. This activity starts from determining the determination of ODGJ in Pabelan village, problem formulation, identification of alternative problem solving, preparation, implementation of activities, practice and simulation, mentoring and ends with evaluation. The results of service activities, namely the knowledge and ability of cadres and families increased in preventing recurrence of ODGJ patients after being given health education and mentoring activities.